1990
DOI: 10.1093/ndt/5.10.847
|View full text |Cite
|
Sign up to set email alerts
|

Renal Siderosis in Patients with Heart-Valve Prostheses: Clinical Implications

Abstract: We have studied the clinical and morphological implications of renal siderosis, reviewing the autopsy protocols of 33 patients with valve prostheses in the heart. Seventeen patients had variable amounts of iron in the proximal tubules of the kidney. Renal siderosis was more frequent in women, in patients with longest time of evolution from the surgical procedure, and in patients with two valve prostheses. Histologically three degrees of renal siderosis may be defined: mild and moderate degrees of iron overload… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…In the urine of these patients with renal siderosis, hemosiderin may be found in tubular epithelial cells. Renal siderosis has been documented in patients with heart valve prostheses (12) (as in the current case). Studies show its association with prolonged intravascular hemolysis (13).…”
Section: Discussionsupporting
confidence: 65%
“…In the urine of these patients with renal siderosis, hemosiderin may be found in tubular epithelial cells. Renal siderosis has been documented in patients with heart valve prostheses (12) (as in the current case). Studies show its association with prolonged intravascular hemolysis (13).…”
Section: Discussionsupporting
confidence: 65%
“…Several, but not all, studies have found an association between high iron burden or increased iron consumption with elevated risk of cardiovascular disease in subjects with or without renal disease [10, 11, 12, 13, 14]. Moreover, iron overload has been linked to the progression of renal disease [15, 16, 17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…hronic iron overload is associated with marked iron deposition in the glomeruli and proximal and distal tubules accompanied by glomerular hypercellularity, mesangial expansion, tubular atrophy, and interstitial fibrosis of the kidneys (Landing et al, 1989;Pardo-Mindan et al, 1990;Zhou, et al, 1996). It is now known that approximately 10% of the American population carry the gene for hemochromatosis, and 1% actually suffer from iron overload (Edwards et al, 1991).…”
mentioning
confidence: 99%